2017
DOI: 10.1515/hmbci-2017-0012
|View full text |Cite
|
Sign up to set email alerts
|

Do exercises improve back pain in pregnancy?

Abstract: Objective To assess the efficacy of an exercise program towards reducing back pain in pregnant women. Methods In this prospective control study, 145 low risk pregnant women who scored more than 20 for functional limitation assessment were recruited. The severity of back pain was assessed using the visual analoque scale (VAS) and the functional limitation was assessed using the Oswestry disability questionnaire (ODQ). All participants were informed of back care measures and provided with Paracetamol as an adjun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In fact, in a recent study performed in pregnant women, the median usage of Paracetamol as an analgesic to control back pain in the control group was 500 mg higher than in the exercise group. 15 Despite the exact mechanisms to explain exerciseinduced hypoalgesia are still unclear, there are potential factors that might explain this lower pain through the concurrent exercise First, it is widely demonstrated that aerobic exercise reduces pain sensitivity across all types of pain, 11 even in populations without chronic pain. 11 One of these mechanisms is the activation of the endogenous opioid system 11 as aerobic exercise may promote the liberation of beta-endorphins, inducing positive changes in pain sensitivity or analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in a recent study performed in pregnant women, the median usage of Paracetamol as an analgesic to control back pain in the control group was 500 mg higher than in the exercise group. 15 Despite the exact mechanisms to explain exerciseinduced hypoalgesia are still unclear, there are potential factors that might explain this lower pain through the concurrent exercise First, it is widely demonstrated that aerobic exercise reduces pain sensitivity across all types of pain, 11 even in populations without chronic pain. 11 One of these mechanisms is the activation of the endogenous opioid system 11 as aerobic exercise may promote the liberation of beta-endorphins, inducing positive changes in pain sensitivity or analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some authors have shown the potential of exercise during pregnancy on reducing backpain intensity and associated disability, 13,14 including less need for analgesia. 15 Notwithstanding, systematic reviews on the topic 14,[16][17][18] suggest that exercise exerts a small protective effect against low back pain during gestation, which might be partially justified by the scarce, equivocal, and low-quality evidence. 14,16 There is also a lack of studies focusing on the effects of exercise on sciatic pain during pregnancy and concerning the best exercise training modality (e.g., aerobic exercise, resistance training, and concurrent exercise) for decreasing pain in this stage of women's life.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that exercise, including deep and super cial lumbopelvic muscles, can help reduce the severity of LPP during pregnancy with an improvement in functional ability [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, almost half of women with initially manifesting LBP continue to have pain until the end of the first year after delivery. Typically, PGP starts by the end of the third month of gestation, with a peak between the twenty fourth and thirty sixth gestational weeks, lasting for about six months after women's self-care activities during puerperium (Abu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%